Geomagnetic Storms and Recording of Acoustic Signals - Belyakov, Askold (Newinera Publisher, 2024)
Having published three articles in the Journal La Multiapp: “Doppler Effect and Acoustic Trails of Neutrinos”, “Neutrinos above the Earth's surface” and “Algorithm for detecting acoustic traces of neutrino decay”, I already wanted to stop research in this direction, if only because that I do not have enough competencies in astrophysics, and that published data is enough for specialized specialists to evaluate the technical and scientific novelty and understand the capabilities of the new method. But, when on the morning of February 3, 2024 at 07:40:19 I turned on the monitoring system, bipolar acoustic pulses with a visible period of 40 μs (frequency 25 kHz) began to be observed on the screen with an interval of about 0.3 seconds, the shape of which is very similar to acoustic traces, associated with neutrino decay. The apparent frequency of these pulses was underestimated by a factor of two, probably due to the insufficiently high Nyquist frequency (50 kHz). A similar picture was observed during the next registration at 07:40:38, and at 07:40:57, only five pulses were recorded with a repetition interval of 1 second. On the fourth and fifth of February there were practically no impulses. There was a suspicion that the observed process was timed to coincide with a geomagnetic storm; more precisely, it was the observed processes that caused geomagnetic storms.